Психологічні умови ефективної психопрофілактичної роботи керівників підрозділів Національної поліції України - Барко, В. І.; Бондарчук, М. Т.; Barko, V. I.; Bondarchuk, M. T. (Право і безпека. - 2016. - № 1 (60). - С. 13-19, 2016)
Охарактеризовано психологічні умови здійснення керівником ефективної психопрофілактичної роботи з поліцейськими. Звернено увагу на те, що діяльність поліцейських належить до числа складних, супроводжується значними фізичними та психологічними навантаженнями на працівників, нерідко несе загрозу для їх життя і здоров’я. Зроблено акцент на ідеї проактивного підходу, який лежить в основі сучасних концепцій поліцейського менеджменту та покликаний забезпечити психологічну профілактику негараздів у поліцейській організації, попередження конфліктів, стресів, невдоволення працівників. Розкрито психологічні умови здійснення керівником проактивного менеджменту, підкреслено необхідність здійснення спеціальної психологічної підготовки управлінців поліції шляхом проведення професійно-психологічних тренінгів.

The psychological conditions of a chief’s effective psychological and preventive work with police units’ officers have been revealed. It is emphasized that police managers’ experience from the developed foreign countries indicates about the growing attention to the study of the psychological factors of the effectiveness of the police work, creation of appropriate conditions for preserving physical and mental health of the personnel, accomplishment of psychological and preventive work. The police activity is among the complex ones, it is accompanied by the significant physical and psychological workload on officers, often includes a threat to their lives and health. Special emphasis is made on the fact that the basis of modern concepts of police management are the ideas of proactive approach, which is aimed at providing psychological prevention of the problems within the police force, prevention of conflicts, stresses, dissatisfaction of officers, etc. It has been established that the psychological conditions of implementation of such a proactive management is the realization of humanist leader-centered approach to police officers; organization of the efficient teamwork and leadership in the units; motivation and promotion of police officers’ work, their personal development. It is the proactive approach to management ensures the high efficiency of police units’ activities, providing the preservation of their physical and psychological health. The authors have indicated that in order its implementation it is important to realize specific professional and psychological training of police chiefs aimed at developing skills of preventive work with the staff, where the effective mean of such training is implementation of police technologies of professional and psychological training into the practice of professional training.

Охарактеризованы психологические условия осуществления руководителем эффективной психопрофилактической работы с полицейскими. Обращено внимание на то, что деятельность полицейских относится к числу сложных, сопровождается значительными физическими и психологическими нагрузками на работников, нередко содержит угрозу для их жизни и здоровья. Сделан акцент на идее проактивного подхода, лежащего в основе современных концепций полицейского менеджмента и призванного обеспечить психологическую профилактику проблем в полицейской организации, предупреждение конфликтов, стрессов, недовольства полицейских. Раскрыты психологические условия осуществления руководителем проактивного менеджмента, подчёркнута необходимость осуществления специальной психологической подготовки управленцев полиции посредством проведения профессионально-психологических тренингов.
Psychological conditions of effective psychological and preventive work accomplished by chiefs of the units of the National police of Ukraine
Психологические условия эффективной психопрофилактической работы руководителей подразделений Национальной полиции Украины
Барко, В. І. Психологічні умови ефективної психопрофілактичної роботи керівників підрозділів Національної поліції України / В. І. Барко, М. Т. Бондарчук // Право і безпека. - 2016. - № 1 (60). - С. 13-19.
Barko, V.I. and Bondarchuk, M.T. (2016), “Psychological conditions of effective psychological and preventive work accomplished by chiefs of the units of the National Police of Ukraine” [“Psykholohichni umovy efektyvnoi psykhoprofilaktychnoi roboty kerivnykiv pidrozdiliv Natsionalnoi politsii Ukrainy”], Pravo i Bezpeka, No. 1, pp. 13–19.
Keywords: Психологія. Рsychology. Психология; юридична психологія; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; психологічні умови; психопрофілактична робота; поліція; керівники; професійно-психологічний тренінг; psychological conditions; psychological and preventive work; police; chiefs; professional and psychological training; психологические условия; психопрофилактическая работа; полиция; руководители; профессионально-психологический тренинг